Particle acceleration in dipolarization events. Issue 5 (6th May 2013) - Birn, J.; Hesse, M.; Nakamura, R.; Zaharia, S.
Abstract : [1] Using the electromagnetic fields of a recent MHD simulation of magnetotail reconnection, flow bursts and dipolarization, we investigate the acceleration of test particles (protons and electrons) to suprathermal energies, confirming and extending earlier results on acceleration mechanisms and sources. (Part of the new results have been reviewed recently in Birn et al., Space Science Reviews, 167, doi:10.1007/ s11214‐012‐9874‐4.) The test particle simulations reproduce major features of energetic particle events (injections) associated with substorms or other dipolarization events, particularly a rapid rise of energetic particle fluxes over limited ranges of energy. The major acceleration mechanisms for electrons are betatron acceleration and Fermi acceleration in the collapsing magnetic field. Ions, although non‐adiabatic, undergo similar acceleration. Two major entry mechanisms into the acceleration site are identified: cross‐tail drift from the inner tail plasma sheet and reconnection entry from field lines extending to the more distant plasma sheet. The former dominates early in an event and at higher energies (hundreds of keV) while the latter constitutes the main source later and at lower energies (tens of keV). Despite the fact that the injection front moves earthward in the tail, the peak of energetic particle fluxes moves to higher latitude when mapped from the near‐Earth boundary to Earth in a static magnetic field model. Key Points: Dipolarization electric field is identified as major acceleration mechanism Cross‐tail drift and reconnection constitute main entries to acceleration site Earthward and poleward propagation of injections are found to be consistent